First radiation hybrid map of the river buffalo X chromosome (BBUX) and comparison with BTAX - Ianella, P. [UNESP]; Venancio, L. P. R. [UNESP]; Stafuzza, N. B. [UNESP]; Miziara, M. N. [UNESP]; Agarwala, R.; Schaffer, A. A.; Riggs, P. K.; Womack, J. E.; Amaral, M. E. J. [UNESP] (Blackwell Publishing, 2008)
We report the first radiation hybrid map of the river buffalo X chromosome generated from a recently constructed river buffalo (Bubalus bubalis) whole-genome radiation hybrid panel (BBURH5000). This map contains a total of 33 cattle-derived markers, including 10 genes, four ESTs and 19 microsatellites. The markers are distributed in two linkage groups: LG1 contains eight markers spanning 125.6 cR, and LG2 contains 25 markers spanning 366.3 cR. LG1 contains six markers in common with bovine sequence assembly BUILD 3.1. With the exception of BMS2152, the order of these markers on our BBUX map is shuffled when compared to the cow X chromosome (Bos taurus; BTAX). From LG2, two markers (AMELX and BL22) map to a more distal portion of BTAX compared to BBUX. In addition, two pairs of LG2 markers exhibit inversions compared to BTAX (ILSTS017 and ATRX; XBM38 and PPEF1). Alternatively, when compared to the most recent bovine RH map (Bov-Gen 3000rads), BL1098 and BMS2227 from LG1 as well as PLS3 and BMS1820 from LG2 showed inverted positions on the BBUX map. These discrepancies in buffalo and cattle maps may reflect evolutionary divergence of the chromosomes or mapping errors in one of the two species. Although the set of mapped markers does not cover the entire X chromosome, this map is a starting point for the construction of a high-resolution map, which is necessary for characterization of small rearrangements that might have occurred between the Bubalus bubalis and Bos taurus X chromosomes.
Keywords: radiation hybrid mapping; River buffalo; X chromosome